Tindak Tutur Lokusi dalam Video Konten Edukasi Channel YouTube Henny Kristianus Bertema Kedewasaan dalam Berfikir - Arshi Vinusia; Annura Sastri Aurasyifa; Muhammad Rakha Jidane Setiawan; Zidan Muhammad Zamzami; Farrah Suryaningtyas; Asep Purwo Yudi Utomo; Ngabiyanto Ngabiyanto (Universitas Palangka Raya, 2026)
The rise of reflective content on YouTube underscores the need for pragmatic research that investigates not only what is said but also the effects of speech on audiences (perlocution). This study aims to analyze the speech act forms associated with perlocutionary effects on Henny Kristianus’s YouTube channel, focusing on the theme of maturity of mind, and to map observable indicators in viewers’ responses. A qualitative descriptive approach with pragmatic content analysis was employed. Data were drawn from transcripts of two videos and corresponding audience comments. The analysis identified three dimensions: (1) types of illocutions (advice, invitation, warning, empathetic assertion), (2) rhetorical/multimodal devices (metaphor, personal narrative, reflective question, call to action), and (3) observable perlocution indicators (attitude change, behavioral intention, emotional support). The findings show that empathetic and reflective utterances most frequently produce perlocutionary effects such as cognitive clarification, behavioral intention, and social reinforcement among viewers. These results suggest that the perlocutionary strength in digital discourse is influenced by the harmony between linguistic strategy, message depth, and communicated maturity values. Theoretically, this research enriches Indonesian digital pragmatics studies. Practically, it provides educators and content creators with insights to design ethical, persuasive, and character-building educational discourse.